2021
DOI: 10.1038/s41467-021-24663-y
|View full text |Cite
|
Sign up to set email alerts
|

Astral hydrogels mimic tissue mechanics by aster-aster interpenetration

Abstract: Many soft tissues are compression-stiffening and extension-softening in response to axial strains, but common hydrogels are either inert (for ideal chains) or tissue-opposite (for semiflexible polymers). Herein, we report a class of astral hydrogels that are structurally distinct from tissues but mechanically tissue-like. Specifically, hierarchical self-assembly of amphiphilic gemini molecules produces radial asters with a common core and divergently growing, semiflexible ribbons; adjacent asters moderately in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…S1 and S2 of ESI. † Notably, our results are in very good agreement with those reported by Xie et al 29 in Fig. 6a of their manuscript for both agarose and polyacrylamide gels and for comparable compressional axial strains (i.e., axial strain r30%).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…S1 and S2 of ESI. † Notably, our results are in very good agreement with those reported by Xie et al 29 in Fig. 6a of their manuscript for both agarose and polyacrylamide gels and for comparable compressional axial strains (i.e., axial strain r30%).…”
supporting
confidence: 92%
“…The viscoelastic properties of hydrogels designed for mimicking biological specimens [26][27][28][29] are fully described by their frequency-dependent shear complex modulus G*(o) = G 0 (o) + iG 00 (o), which is a complex number whose real (G 0 (o), also known as storage modulus) and imaginary (G 00 (o), also known as loss modulus) parts provide valuable information on the elastic and viscous nature of the sample, respectively. Conventionally, these are determined via oscillatory measurements performed by means of rotational rheometers.…”
mentioning
confidence: 99%
“…32 Another study used self-assemblies of synthetic colloids made of amorphous core and radial crystalline ribbons to obtain hydrogels through colloid−colloid interpenetration. 33 Extension-softening and compression-stiffening mechanical responses that mimic biological tissues were observed by controlling the interpenetration of these densely packed colloids. 33 Moreover, hierarchically structured anisotropic hydrogels of poly(vinyl alcohol) (PVA) nanofibrils obtained through freezing and salting out of PVA solution demonstrated a two-to fourfold improvement in strength and toughness, compared to a nonfibril chemically cross-linked PVA hydrogel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zarket and Raghavan demonstrated that a cross-linked alginate gel exhibits different mechanical responses to compression when its onion-like shell comprises layers with different chemical compositions . Another study used self-assemblies of synthetic colloids made of amorphous core and radial crystalline ribbons to obtain hydrogels through colloid–colloid interpenetration . Extension-softening and compression-stiffening mechanical responses that mimic biological tissues were observed by controlling the interpenetration of these densely packed colloids .…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic modification of the hydrogel polymeric network can mimic the biochemical and physical properties of the ECM, enabling cell loading and repair of damaged tissue. The selection of precursors with good biocompatibility to prepare hydrogels is a prerequisite for successful applications, such as biological components [ 8 , 9 , 10 , 11 ] or inert polymers [ 12 , 13 ]. Excellent water retention capacity is the most notable feature of hydrogels, which lays the foundation for mimicking the softness and water content of ECM [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%